1998
DOI: 10.1002/(sici)1521-3757(19980619)110:12<1792::aid-ange1792>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

trans-[RuCl2(phosphan)2(1,2-diamin)]- und chiraletrans-[RuCl2(diphosphan)(1,2-diamin)]- Komplexe: lagerstabile Katalysatorvorstufen für die schnelle, produktive und stereoselektive Hydrierung von Ketonen

Abstract: Eine Umsatzzahl (TON) von 2 400 000 und einen Umsatz pro Zeit (TOF) von 63 s−1 ermöglicht der chirale RuII‐Komplex 1 (R=p‐H3CC6H4) als Katalysator bei der asymmetrischen Hydrierung von Acetophenon. Mit verwandten RuII‐Katalysatoren werden α,β‐ungesättigte Ketone selektiv an der Carbonylgruppe asymmetrisch hydriert und aus 4‐substituierten Cyclohexanonen die entsprechenden cis‐Alkohole erhalten.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0
20

Year Published

1998
1998
2001
2001

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 28 publications
2
63
0
20
Order By: Relevance
“…[7] At each step, the unreacted materials were removed by washing with DMA. The 31 P NMR analysis [8] of the solid suggested that the resulting diphosphine/diamine mixed-ligand Ru complex (R,RR)-3a was a 7 : 1 mixture of the trans-dichloro complex (singlet at 47.5 ppm) and its cis isomer (broad singlets at 50.0 and 57.5 ppm) contaminated with unreacted (R)-1a (±15.8 ppm) and some unknown compounds. The purity of the diphosphine/diamine Ru complex was ca.…”
Section: Synthesis Of Precatalystsmentioning
confidence: 99%
See 4 more Smart Citations
“…[7] At each step, the unreacted materials were removed by washing with DMA. The 31 P NMR analysis [8] of the solid suggested that the resulting diphosphine/diamine mixed-ligand Ru complex (R,RR)-3a was a 7 : 1 mixture of the trans-dichloro complex (singlet at 47.5 ppm) and its cis isomer (broad singlets at 50.0 and 57.5 ppm) contaminated with unreacted (R)-1a (±15.8 ppm) and some unknown compounds. The purity of the diphosphine/diamine Ru complex was ca.…”
Section: Synthesis Of Precatalystsmentioning
confidence: 99%
“…Both trans-and cis-RuCl 2 [(R)-binap][(R,R)-dpen] are known to be reactive for homogeneous hydrogenation of ketones. [8] As shown in Figure 1, the polymer beads are better swelled in DMF than in 2-propanol, which serves as a standard solvent of hydrogenation. [4] DMA can also be used in place of DMF.…”
Section: Synthesis Of Precatalystsmentioning
confidence: 99%
See 3 more Smart Citations